2003
DOI: 10.3310/hta7130
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of atypical antipsychotic drugs in schizophrenia

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
2
7

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(131 citation statements)
references
References 513 publications
6
114
2
7
Order By: Relevance
“…A recent systematic review suggests that the conclusions that could be drawn about the relative effectiveness of the newer antipsychotics were limited because of problems with the validity of the trials in terms of inclusion and exclusion criteria, dose used, sample size and duration of trials, outcome measures used and methods of reporting symptoms. 32 In addition, the majority of trials compare the newer atypicals to haloperidol, a drug not widely used in Europe or the UK. The side-effect profile of haloperidol, particularly used at high doses, may not be representative of that found with other typical antipsychotics.…”
Section: Therapeutic Efficacymentioning
confidence: 99%
“…A recent systematic review suggests that the conclusions that could be drawn about the relative effectiveness of the newer antipsychotics were limited because of problems with the validity of the trials in terms of inclusion and exclusion criteria, dose used, sample size and duration of trials, outcome measures used and methods of reporting symptoms. 32 In addition, the majority of trials compare the newer atypicals to haloperidol, a drug not widely used in Europe or the UK. The side-effect profile of haloperidol, particularly used at high doses, may not be representative of that found with other typical antipsychotics.…”
Section: Therapeutic Efficacymentioning
confidence: 99%
“…37 It produces few acute EPS and has a lower incidence of tardive dyskinesia (TD) than other antipsychotics, although other ADRs include sedation, hypersalivation and hypertension. [44][45][46] Regarding efficacy, the HTA review of atypical antipsychotics in schizophrenia 47 noted that evidence for the effectiveness of the atypicals compared with typicals was 'in general of poor quality, based on short term trials and difficult to generalise to the whole population of people with schizophrenia'. The more recent Clinical Antipsychotic Trials in Intervention Effectiveness (CATIE) 43 and Cost Utility of the Latest Antipsychotic Drugs in Schizophrenia Study (CUtLASS) trials 48 have led the chief investigators of these trials to conclude that typical antipsychotics are as good as atypical antipsychotics for many patients.…”
Section: Schizophreniamentioning
confidence: 99%
“…Several meta-analyses of RCTs have shown that atypical antipsychotics are less likely to cause EPS than conventional agents (Bagnall et al, 2003;Geddes et al, 2000). The EPS advantage of the atypical antipsychotics was the major reason why the National Institute of Clinical Excellence (NICE) Schizophrenia Guideline in the UK recommended that atypical antipsychotics should be first line drugs in the treatment of those with newly diagnosed schizophrenia and that patients treated with conventional antipsychotics who have unacceptable EPS should be switched to an atypical agent (National Institute for Clinical Excellence, 2002).…”
Section: Differential Risk Of Eps Among Antipsychotic Drugsmentioning
confidence: 99%